The role of the mTOR pathway in diabetic retinopathy - Casciano, Fabio; Zauli, Enrico; Rimondi, Erika; Mura, Marco; Previati, Maurizio; Busin, Massimo; Zauli, Giorgio (Frontiers in Medicine, 2022)
The retina, the part of the eye, translates the light signal into an electric current that can be sent to the brain as visual information. To achieve this, the retina requires fine-tuned vascularization for its energy supply. Diabetic retinopathy (DR) causes alterations in the eye vascularization that reduce the oxygen supply with consequent retinal neurodegeneration. During DR, the mammalian target of rapamycin (mTOR) pathway seems to coordinate retinal neurodegeneration with multiple anabolic and catabolic processes, such as autophagy, oxidative stress, cell death, and the release of pro-inflammatory cytokines, which are closely related to chronic hyperglycemia. This review outlines the normal anatomy of the retina and how hyperglycemia can be involved in the neurodegeneration underlying this disease through over activation or inhibition of the mTOR pathway.